Nisp as a potential surface anchor for pandemic H1N1 2009 Haemagglutinin (HA1) viral epitope in Lactococcus lactis - Siaw, Stella Xiu Joan (2014)
The rapid worldwide spread of the pandemic H1N1 2009 influenza A virus in the early 2009 has contributed to high morbidity and mortality especially in children, the elderly and immuno-compromised individuals. Current available influenza vaccines are effective in terms of providing immunity protection but there are several limitations and disadvantages such as allergic reactions, biosafety issues and limited production capacity. This study uses Lactococcus lactis as a vehicle for cloning of the haemagglutinin (HA1) epitope of the pandemic H1N1 2009 influenza virus. The HA1 epitope was amplified and cloned into a L. lactis vector together with the usp45 signal peptide and nisP anchor protein (nisP-anc) in order to assemble a surface displayed HA1 recombinant L. lactis. The recombinant L. lactis were able to express HA1 epitope protein when induced with nisin and was further confirmed with Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) analysis. The recombinant host cells were further examined by using whole cell ELISA, fluorescence microscopy and flow cytometry to detect the surface displayed HA1 epitope protein on their surfaces. Despite it could not be confirmed that HA1 epitope has been successfully surface displayed, the recombinant cells were fed to BALB/c mice host to observe for its capability to induce immunogenic response. From the analysis of antigen-specific serum antibody by sandwich ELISA, significant anti-HA1 sIgA antibody was produced in the mice fecal suspension of mice group NZ9000 (pNZ:HN) when compared to the negative control NZ9000 (pNZ8048) suggesting that high specific anti-HA1 sIgA antibody was produced in the mice rectum. This study was conducted to gain more insights of the potential of L. lactis as a vaccine vehicle and future optimization can be adopted to further enhance its capability in vaccine delivery.